2007
DOI: 10.1118/1.2790585
|View full text |Cite
|
Sign up to set email alerts
|

Realtime light dosimetry software tools for interstitial photodynamic therapy of the human prostate

Abstract: Photodynamic therapy (PDT) for the treatment of prostate cancer has been demonstrated to be a safe treatment option capable of inducing tissue destruction and decreasing prostate specific antigen (PSA) levels. However, prostate-PDT results in large intra- and interpatient variations in treatment response, possibly due to biological variations in tissue composition and short-term response to the therapeutic irradiation. Within our group, an instrument for interstitial PDT on prostate tissue has been developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 47 publications
2
69
0
2
Order By: Relevance
“…The group in Lund, Sweden is developing a multiple channel system of point sources that can be used as either light sources or detectors. 107 A personal computer controls the position and duration of the point sources to optimize light fluence distribution. Another group in Toronto, Canada has commercialized a four-channel light source with computerized power control in each channel.…”
Section: Ivd Treatment Planning Integrated With Dosimetry Imagingmentioning
confidence: 99%
“…The group in Lund, Sweden is developing a multiple channel system of point sources that can be used as either light sources or detectors. 107 A personal computer controls the position and duration of the point sources to optimize light fluence distribution. Another group in Toronto, Canada has commercialized a four-channel light source with computerized power control in each channel.…”
Section: Ivd Treatment Planning Integrated With Dosimetry Imagingmentioning
confidence: 99%
“…et al, 2009). Hence, it is often replaced by diffusion theory, when homogeneous light-tissue interaction coefficients are assumed (Altschuler et al, 2005;Rendon, 2008), or diffusion theory in combination with the finite element method (Davidson et al, 2009;Johansson et al, 2007). Unfortunately, neither approach provides the flexibility desired for treatment planning.…”
Section: Computational Framework For Light Dosimetrymentioning
confidence: 99%
“…Other groups have previously proposed using the Cimmino feasibility algorithm (Censor et al 1988) to optimize the diffuser outputs (Altschuler et al 2005, Johansson et al 2007. However, De Pierro and Iusem (1985) have shown that, for the inconsistent case, the Cimmino algorithm minimizes (2.8) rather than (2.5), making the comparison of different diffuser positions in the outer loops inconsistent.…”
Section: Inner Loop-mentioning
confidence: 99%
“…Recently, Johansson et al (2007) have tested their on-line dosimetry system by simulating (based on finite element methods) heterogeneous changes in the optical properties by adding small random changes in the absorption coefficient over and otherwise constant field, and calculating new irradiation times for their treatment fibres using a Cimmino algorithm. In agreement with our results, they find that prostate coverage can be nearly recovered to nominal values.…”
Section: Uncertainties In μ Eff and Diffuser Placementmentioning
confidence: 99%
See 1 more Smart Citation